Global and regional dynamics in knowledge flows and innovation - Van Egeraat, Chris; Kogler, Dieter F., 1973-; Cooke, Philip (Philip N.); Innovation Management (Firm) (London Routledge, 2014)
Innovation, which in essence is the generation of knowledge and its subsequent application in the marketplace in the form of novel products and processes, has become the key concept in inquiries concerning the contemporary knowledge based economy. Geography plays a decisive role in the underlying processes that enable and support knowledge formation and diffusion activities and specific geographical characteristics are considered especially important in this context. However, more recently, attention has focussed on external knowledge inputs
Introduction: Global and Regional Dynamics in Knowledge Flows and Innovation Networks Chris van Egeraat and Dieter F. Kogler 1. Qualitative Analysis and Comparison of Firm and System Incumbents in the New ICT Global Innovation Network Philip Cooke 2. The Evolution of the Wind Industry and the Rise of Chinese Firms: From Industrial Policies to Global Innovation Networks Pedro Campos Silva and Britta Klagge 3. Foreign and Indigenous Innovation in China: Some Evidence from Shanghai Seamus Grimes and Debin Du 4. Mapping Knowledge Space and Technological Relatedness in US Cities Dieter F. Kogler, David L. Rigby and Isaac Tucker 5. Firm Building and Entrepreneurship in Second-Tier High-Tech Regions Heike Mayer 6. Differentiated Knowledge Bases and the Nature of Innovation Networks Roman Martin 7. Social and Spatial Structures of Innovation in the Irish Animation Industry Chris van Egeraat, Sean O'Riain and Aphra Kerr 8. The Geography and Structure of Global Innovation Networks: A Knowledge Base Perspective Ju Liu, Cristina Chaminade and Bjorn Asheim
Includes index.
Keywords: Innovation management